A Scenario for the Critical Fluctuations near the Transition of Few-Bilayer Films of High-Temperature Cuprate Superconductors - Martín M. Botana; Manuel V. Ramallo (Nanomaterials, 2022)
We study the critical fluctuations near the resistive transition of very thin films of high-temperature cuprate superconductors composed of a number <semantics>N</semantics> of only a few unit cells of superconducting bilayers. For that, we solve the fluctuation spectrum of a Gaussian–Ginzburg–Landau model for few-bilayers superconductors considering two alternating Josephson interlayer interaction strengths, and we obtain the corresponding paraconductivity above the transition. Then, we extend these calculations to temperatures below the transition through expressions for the Ginzburg number and Kosterlitz–Thouless-like critical region. When compared with previously available data in <semantics>YBa2</semantics><semantics>Cu3</semantics><semantics>O7−δ</semantics> few-bilayers systems, with <semantics>N</semantics> = 1 to 4, our results seem to provide a plausible scenario for their critical regime.